2017
DOI: 10.1080/00405000.2017.1301019
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in three-dimensional pressure relieving cushions for the prevention of pressure ulcers

Abstract: Polyurethane (PU) foam is one of the most common materials used in the development of pressure relieving cushions. However, it suffers from reduced efficiency in terms of thermophysiological comfort, cost, recycling and importantly, creating a suitable environment for the prevention of pressure ulcers. The paper presents research carried out at the University of Bolton, in the development of pressure relieving cushion applications using three-dimensional (3D) warp knitted spacer fabrics. This research includes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…According to national standards for soft foam polymer hardness, 25% IFD is usually used to characterize the hardness of the material; 65% IFD to characterize the support of the material in deep compression; and 65%/25% is the SF to characterize the bottom support, comfort, etc. 21…”
Section: Evaluation Indicatorsmentioning
confidence: 99%
“…According to national standards for soft foam polymer hardness, 25% IFD is usually used to characterize the hardness of the material; 65% IFD to characterize the support of the material in deep compression; and 65%/25% is the SF to characterize the bottom support, comfort, etc. 21…”
Section: Evaluation Indicatorsmentioning
confidence: 99%
“…Many other special structures have also been developed and studied. [108][109][110][111][112][113] Spacer fabrics also known as three dimensional fabrics, consists of two separate textile sheets (which are kept connected vertically with spacer yarn), have positive qualities for their potential use in edema treatment. 108,109 These spacer fabrics can be manufactured with different methods i.e.…”
Section: Fabric Structurementioning
confidence: 99%
“…The suitability of WKSF for pressure ulcer protection has been studied by several research groups. Hepburn et al [17] compared the pressure relieving cushion effect of WKSF and PU foams and found that WKSFs retained their thickness over longer periods to a larger extent than PU foams under both static and dynamic loading conditions. This is mainly due to superior resilience of the fiber material in the WKSFs.…”
Section: Introductionmentioning
confidence: 99%